World Checklist of Opiliones species (Arachnida). Part 2: Laniatores – Samooidea, Zalmoxoidea and Grassatores incertae sedis - Kury, Adriano Brilhante (2015)
Including more than 6500 species, Opiliones is the third most diverse order of Arachnida, after the megadiverse Acari and Araneae. This database is part 2 of 12 of a project containing an intended worldwide checklist of species and subspecies of Opiliones, and it includes the members of the suborder Laniatores, infraorder Grassatores of the superfamilies Samooidea and Zalmoxoidea plus the genera currently not allocated to any family (i.e. Grassatores incertae sedis). In this Part 2, a total of 556 species and subspecies are listed.